2005
DOI: 10.2111/1551-5028(2005)58[466:dogtgp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Grazed Tussock Grass Populations in Patagonia

Abstract: The cover of Festuca gracillima (coiró n fueguino), a native tussock grass that dominates grass steppes of Southern Patagonia and Tierra del Fuego, has diminished under continuous sheep grazing. This loss is a concern, because it also reduces forage availability in winter, biodiversity, and soil stability. In the present study, the hypothesis that tussock grass birth and mortality rates are balanced only under moderate-grazing or exclusion regimes was tested with two 5-year records of demographic data obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
2
26
0
2
Order By: Relevance
“…This is consistent with César () and Oliva et al. () who found that larger grass tussocks produced new individuals by fragmentation. The process of tussock fragmentation has never been thoroughly analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with César () and Oliva et al. () who found that larger grass tussocks produced new individuals by fragmentation. The process of tussock fragmentation has never been thoroughly analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…Tall tussocks dominate large areas of tropical and subtropical highlands (Cuatrecasas, 1968;Hedberg, 1964;Hnatiuk, 1994;Löffler, 1979;Ramsay and Oxley, 1997) and extend into cool maritime climates of the southern hemisphere temperate zone (Mark et al, 2000;Oliva et al, 2005). Their dominance seems to be associated with year round cold climate but otherwise quite different soil moisture regimes from very wet (New Guinea, New Zealand, Ecuador) to rather dry, even semi-arid, as is the case in the NW-Argentinean and the Bolivian Altiplano (Geyger, 1985;Halloy, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…1994; Ash et al . 1997; Lauenroth & Aguilera 1998; Orr 1998; Milton & Dean 2000; Oliva et al . 2005) because it depends on several environmental variables being simultaneously favourable (O’Connor 1996).…”
Section: Introductionmentioning
confidence: 99%